Resuscitative endovascular balloon occlusion of the aorta management guided by a novel handheld pressure transducer. Issue 4 (15th April 2022) - Holtestaul, Torbjorg; Jones, Ian; Conner, Jeffrey; Lammers, Daniel; Weiss, Jessica; Bingham, Jason; Martin, Matthew J.; Eckert, Matthew
Abstract : REBOA resuscitation requires arterial pressure monitoring that can be logistically challenging in austere settings. The Compass Device is a portable pressure monitor that provides an accurate alternative to guide REBOA resuscitation. Abstract : BACKGROUND: Management of noncompressible truncal hemorrhage using resuscitative endovascular balloon occlusion of the aorta (REBOA) requires arterial pressure monitoring that can be logistically challenging in austere or emergency settings. Novel pressure transducer devices such as the Centurion Compass device (CD) (Medline, Northfield, IL) offer an alternative to traditional monitoring systems. We sought to assess the feasibility of maintaining permissive hypotension during intermittent REBOA in a porcine model guided by CD monitoring. METHODS: Eight Yorkshire swine underwent 20% hemorrhage with an uncontrolled iliofemoral vascular injury. Time-based intermittent zone 1 REBOA was performed with volume-based resuscitation to maintain permissive hypotension. Proximal mean arterial pressures (MAPs) from a carotid arterial line (AL) were obtained and compared with CD readings from the proximal REBOA port. The operator was blinded to AL MAP, and the REBOA was managed with exclusively the CD. RESULTS: Mean survival time was 100 minutes (range, 41–120 minutes) from injury. Arterial line and CD measurements were closely correlated ( r = 0.94, p < 0.001). Bland-Altman analysis for comparison of clinical measurements demonstrated a mean difference of 6 mm Hg (95% confidence interval, −22 to 34 mm Hg) for all MAPs, with a mean difference of 3 mm Hg (95% confidence interval, −6 to 12 mm Hg) in a clinically relevant MAP of <65 mm Hg subset. CONCLUSION: The CD represents a miniaturized and portable arterial pressure monitor that provides an accurate alternative to logistically burdensome AL monitoring to guide REBOA use. The device is highly accurate even at hypotensive pressures and can be used to guide intermittent REBOA strategies. Abstract :